Sustained utilisation of acquired entrepreneurial skills among youth in Southwestern Nigeria: National Directorate of Employment’s perspective (2019)
Entrepreneurial skills are recognized as veritable tools for reducing youth unemployment in Nigeria. However, for it to produce required effects, the extent to which such skills are sustainably used must be ascertained. This study therefore investigated the sustained utilisation of acquired entrepreneurial skills among youth in Southwestern Nigeria from the perspective of National Directorate of Employment. Multistage sampling procedure was used to select 163 respondents for the study from Ogun and Osun States. Data were collected using structured questionnaires and were analyzed using descriptive statistics. The results show that respondents had training on poultry production (17.1%), grasscutter production (11.6%) and trading (9.2%) among others. Also 32.5% of the participants did not diversify into any activity while others diversified into activities such as okada riding, trading, sales of recharge cards, barbing, farming, and computer operator while some also got job. Almost all the participants (99.3%) completed the training, about 88.9% were given take off grant or materials and 96.9% had been able to put the learnt skill to use. Sustained utilisation of acquired NDE entrepreneurial skills was high (73.4%). The study concluded that NDE entrepreneurial skills are sustainably used. It is recommended that the sustainably used components of NDE activities be developed as a package and adapted by organisations engaging in similar training programme.